The The Influence of Fear of Missing Out (FOMO) and Live Streaming on Impulsive Purchases, with Shopee Pay-Later as a Moderating Variable, Among Gen Z in Indonesia - Baiq Nanda Khaerunnisa; Sulhaini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Advances in digital technology have significantly transformed consumer behaviour, particularly in online shopping through e-commerce and social commerce. In Indonesia, internet penetration has reached 80.66%, with approximately 229.4 million users, accelerating the growth of digital consumption. This study aims to analyse the effect of live streaming on Fear of Missing Out (FOMO) and impulsive buying, as well as the moderating role of Shopee Pay-Later among Generation Z in Indonesia. This research adopts a quantitative approach using a survey method involving 100 Generation Z respondents who actively use e-commerce, watch live streaming, and have made online purchases, with purposive sampling and data analysed using SEM-PLS. The findings reveal that live streaming has a positive and significant effect on both FOMO and impulsive buying, and FOMO also positively influences impulsive buying behaviour. However, Shopee Pay-Later does not moderate the relationship between live streaming, FOMO, and impulsive buying. These results indicate that impulsive buying behaviour among Generation Z is more strongly driven by emotional factors and interactive live streaming experiences than by the convenience of digital payment features. This study supports the Stimulus Organism Response (SOR) theory and provides practical implications for e-commerce practitioners to design more interactive and responsible marketing strategies. Kata Kunci: live streaming, Fear of Missing Out (FOMO), impulsive buying, Shopee Pay-Later, Generation Z.